2021
DOI: 10.3168/jds.2020-19679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the circadian rhythm on milk composition in dairy cows: Does day milk differ from night milk?

Abstract: Metabolism in most organisms can show variations between the day and night. These variations may also affect the composition of products derived from livestock. The aim of the present study was to investigate the difference in composition between the day milk and night milk of dairy cows. Ten multiparous Holstein cows (milk yield = 25.2 ± 5.00 kg/d) were randomly selected during mid lactation. Milk samples were collected at 0500 h ("night milk") and 1500 h ("day milk") and analyzed to determine their compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Previous studies reported that antioxidant activity in milk was improved significantly in cows fed diets supplemented with flavonoids [ 30 , 31 ]. As a marker of oxidative stress, MDA can indicate a counterbalance to high levels of oxidative phosphorylation [ 32 ]. The DPPH is a relatively stable organic radical widely used to test samples for its ability to scavenge free radicals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that antioxidant activity in milk was improved significantly in cows fed diets supplemented with flavonoids [ 30 , 31 ]. As a marker of oxidative stress, MDA can indicate a counterbalance to high levels of oxidative phosphorylation [ 32 ]. The DPPH is a relatively stable organic radical widely used to test samples for its ability to scavenge free radicals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In dairy cows, as in other organisms, most physiological parameters show a circadian output affected by photoperiod [ 15 , 16 ]. This has prompted investigations of within-day variations in milk composition, to differentiate between DM and NM from health-promoting, nutritional, and commercial perspectives [ 17 , 29 , 30 , 31 , 32 , 38 ]. As expected, most of these studies found circadian oscillation in milk yield and in some of the milk’s constituents, yet the presence and extent of the circadian variation varied between studies and depended on milking and feeding frequency [ 17 , 29 , 30 , 31 , 32 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted investigations of within-day variations in milk composition, to differentiate between DM and NM from health-promoting, nutritional, and commercial perspectives [ 17 , 29 , 30 , 31 , 32 , 38 ]. As expected, most of these studies found circadian oscillation in milk yield and in some of the milk’s constituents, yet the presence and extent of the circadian variation varied between studies and depended on milking and feeding frequency [ 17 , 29 , 30 , 31 , 32 , 38 ]. In this study, we mainly focused on the composition of fatty acids, due to their high nutritional value [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations